Promote Osseointegration Through Surface Functionalization of Ti-Zr Alloy by Nano Composite Fiber - Amjed Al-khateeb; Emad Al-Hassani; Akram Jabur; Suriani Binti Abu Bakar (Engineering and Technology Journal, 2023)
Using bioactive and biocompatible coatings to biofunctionalized metallic implant surfaces for enhanced bone regeneration while resisting bacterial infection has attracted materials scientists' interest. Bio-metallic Ti-25Zr disc sample was prepared using powder metallurgy and then coated using an electrospinning method to form a nanocomposite fiber as a coating layer over the surface of the metal alloy substrate. Three nano-compounds (Nano-hydroxyapatite, Nano-Titanium dioxide, Nano-strontium titanite) were added individually to the Polycaprolactone/Chitosan blend to prepare the electrospinning solutions. The results show a significant improvement in biocompatibility for the coated samples after seven days of (MC3T3-E1) cell culture. Cell viability percentages were significantly higher for the coated samples compared to uncoated ones, with values of PCL/Chitosan/nHA (HA1) has 239.45±17.95%, PCL/Chitosan/nSrTiO3 (SR1)  has170.09±8.12%, and PCL/Chitosan/nTiO2 (TI1)  has 117.19±19.42%, while bare Ti-25Zr has 80.52±1.97%. Cell proliferation also shows a remarkable increase with time for coated samples, and the enhancement reaches 197.76% for (HA1), 111.38% (SR1), and 45.81 % (TI1) in comparison with (bare Ti-25Zr). For the antibacterial test, no inhibition zone for the control sample (bare Ti-25Zr) was observed, while the coated samples showed a suitable and comparable inhibition zone. The coating procedure is simple and inexpensive, and composite nano-fiber has high biocompatibility and promise in orthodontic and orthopedic bone regeneration.